The role of research bodies, from leaders of the system to responsible partners - Sonnino A.; Carrabba P.; Iannetta M. (Innovation in the Mediterranean agrifood sector. Concepts, experiences and actors in a developing ecosystem, 2016)
They were once the central element in state-funded research, but now the research bodies need to redefine their role as partners in the innovation process, responding more efficiently to the needs of society and businesses. In agriculture, the concept of innovation was dominated in the past by linear knowledge transfer in the form of new technologies that were essentially generated by public research (research institutes or universities), transferred to the agricultural extension services, and hence to the farmers for adoption. Therefore, the knowledge generated was transferred between the actors by means of mechanisms that were mostly one-directional (conferences, articles in scientific journals or technical publications etc.). This model has achieved successes, but it is equally undeniable that the innovation context in agriculture has changed radically in three ways. The challenges are increasingly complex, many new actors have burst onto the innovation stage in agriculture, e.g. the third sector organisations and producers’ associations, and the general public is also demanding a more active role in the decision-making processes related to the adoption of technological innovations. The chapter offers an outlook for renewal of the agricultural innovation systems based on the Responsible Research and Innovation pillars (RRI).